ChemInform Abstract: Catalytic Highly Enantioselective Vinylogous Povarov Reaction. Issue 21 (2nd May 2013) - Caruana, Lorenzo; Fochi, Mariafrancesca; Ranieri, Silvia; Mazzanti, Andrea; Bernardi, Luca
Abstract A series of chiral tetrahydroquinolines (III) is prepared with high diastereo‐ and enantioselectivity by a hitherto not described Povarov reaction of imines (I) with acylaminobutadienes (II).